HGG-36. ONC201 TARGETING IN DIPG - Abuarqoub, Alqassem (Neuro Oncol, 2021)
Diffuse intrinsic pontine glioma (DIPG) is a group of predominantly pediatric brain tumors with an average age of diagnosis of 6–7 years old, and a poor prognosis (median survival of ~1 year). Given the location of DIPG in the brainstem, surgical approaches are limited. Furthermore, the tumors have limited responsivity to traditional chemotherapy or radiotherapy, ergo new therapeutic options are needed. Recently, the drug ONC201 has emerged as a potential therapeutic option with outcomes sometimes surpassing progression-free and expected survival outcomes. However, the selectivity of its effect and mechanism in DIPG is still unclear. Here, we pursue a better understanding of ONC201 and its mechanism of action directly in DIPG patient-derived cell lines. First, we demonstrate that a range of DIPG cell lines are highly sensitive to ONC201 and compare this sensitivity to other patient-derived brain tumor and normal controls. Next, we directly show that the mitochondrial protease, ClpP is the primary target of ONC201 in DIPG. Given recent literature implicating the activation of ClpP by ONC201 and dysregulation of the metabolome in other tumors, we are currently examining these downstream effects in DIPG. Ultimately we hope to elucidate whether ClpP targeting can be used to better diagnose and improve therapeutic options in DIPG